1957
DOI: 10.1104/pp.32.3.197
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Fixation of CO2 by Succulent Leaves: Metabolic Changes Subsequent to Initial Fixation.

Abstract: The methods used in these longer periods of dark fixation of C1402 are the same as those described in detail in a previous communication (15). A specially constructed apparatus permits excised leaves from B. calycinum to be exposed to C1402 in total darkness. Approximately one gm of young leaves taken from the apex of the plants immediately before use was placed in the apparatus, C1402 generated from 4 to 5 mg of BaC'403 (specific activity 0.0282 mc/mg) was admitted, and the reaction terminated at the desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…This hypothesis is consistent with reports of dark fixation in which malate and aspartate are the first detectable labeled products (2,15,16), and with data indicating that in maize roots the rate of fixation of CO2 into a water soluble fraction is correlated with the rate of protein synthesis (16). In addition, atmospheric CO2 levels have been shown to stimulate the incorporation of labeled leucine into an ethanol insoluble residue from carrot and tomato roots (16), and it has been reported that malate can replace CO2 in stimulating the growth of etiolated coleoptiles (1).…”
Section: C02-stimulated Protein Synthesissupporting
confidence: 79%
“…This hypothesis is consistent with reports of dark fixation in which malate and aspartate are the first detectable labeled products (2,15,16), and with data indicating that in maize roots the rate of fixation of CO2 into a water soluble fraction is correlated with the rate of protein synthesis (16). In addition, atmospheric CO2 levels have been shown to stimulate the incorporation of labeled leucine into an ethanol insoluble residue from carrot and tomato roots (16), and it has been reported that malate can replace CO2 in stimulating the growth of etiolated coleoptiles (1).…”
Section: C02-stimulated Protein Synthesissupporting
confidence: 79%
“…Nocturnal '4C02 assimilation profiles indicate that various metabolites are labeled, especially aspartate, alanine, and intermediates ofthe citric acid cycle (17,23). The percentage of the label that accumulates in these components relative to malate, however, is low.…”
mentioning
confidence: 99%
“…The methods used in the study of the dark fixation of CO2 in intact spinach leaves are the same as those detailed in earlier communications (8,9). Spinach leaves were obtained commercially and thoroughly washed in distilled water and blotted dry; 1 g of young leaves was placed in an apparatus which permits exposure to the C140., in total darkness.…”
mentioning
confidence: 99%
“…It will be shown in this paper that the effects of sodium chloride can be reversed by adding oxidized or reduced diphosphopyridine nucleotide (DPN+, DPNH). Two possible mechanisms are advanced to explain the (9). Radioactive compounds were located by exposing the chromatogram to no-screen X-ray film.…”
mentioning
confidence: 99%